How medical dominance and interprofessional conflicts undermine patient-centred care in hospitals: historical analysis and multiple embedded case study in Morocco - Bart Criel; Zakaria Belrhiti; Sara Van Belle (BMJ Global Health, 2021)
Background In Morocco’s health systems, reforms were accompanied by increased tensions among doctors, nurses and health managers, poor interprofessional collaboration and counterproductive power struggles. However, little attention has focused on the processes underlying these interprofessional conflicts and their nature. Here, we explored the perspective of health workers and managers in four Moroccan hospitals.Methods We adopted a multiple embedded case study design and conducted 68 interviews, 8 focus group discussions and 11 group discussions with doctors, nurses, administrators and health managers at different organisational levels. We analysed what health workers (doctors and nurses) and health managers said about their sources of power, perceived roles and relationships with other healthcare professions. For our iterative qualitative data analysis, we coded all data sources using NVivo V.11 software and carried out thematic analysis using the concepts of ‘negotiated order’ and the four worldviews. For context, we used historical analysis to trace the development of medical and nursing professions during the colonial and postcolonial eras in Morocco.Results Our findings highlight professional hierarchies that counterbalance the power of formal hierarchies. Interprofessional interactions in Moroccan hospitals are marked by conflicts, power struggles and daily negotiated orders that may not serve the best interests of patients. The results confirm the dominance of medical specialists occupying the top of the professional hierarchy pyramid, as perceived at all levels in the four hospitals. In addition, health managers, lacking institutional backing, resources and decision spaces, often must rely on soft power when dealing with health workers to ensure smooth collaboration in care.Conclusion The stratified order of care professions creates hierarchical professional boundaries in Moroccan hospitals, leading to partitioning of care and poor interprofessional collaboration. More attention should be placed on empowering health workers in delivering quality care by ensuring smooth interprofessional collaboration.